Hubungan Waktu Tanggap Dengan Tingkat Kecemasan Keluarga Pasien Dengan Triase Merah Dan Kuning Di IGD RSUD Kota Tanjungpinang - Suparyani Suparyani; Fitriani Suangga; Siska Natalia (An-Najat, 2023)
Phenomena that occur in patients under treatment, especially in the emergency department, can indirectly trigger anxiety for families and patients. This is because the patient's condition is at risk of the threat of disability and death, which makes the patient and family want to receive immediate treatment in the ER. Meanwhile, response time is carried out with one flow and problem priority. This study aims to determine the relationship between response time and the anxiety level of the families of patients with red and yellow triage in the emergency room at Tanjungpinang City Regional Hospital. The design of this research is quantitative correlational. Accidental sampling technique was used to obtain 55 respondents. The data was analyzed using the chi square test. The results of univariate data analysis found that the response time showed that the response time was fast for 38 respondents (69.1%), and the response time was slow for 17 respondents (30.9%) and the level of mild anxiety was 43 respondents (78.2%), and the patient's family had a moderate level of anxiety. 12 respondents (21.8%). There is a relationship between response time and the anxiety level of the patient's family with red and yellow triage with a p value of 0.000 (<0.05). It is hoped that the hospital can provide written information regarding patient treatment priorities and the maximum time for carrying out triage in the ER so that every patient who comes can understand the condition. Triage training for nurses in the ER has been improved to make them more skilled and competent.